GASTROGRAFFIN USE IN DISTAL INTESTINAL OBSTRUCTION SYNDROME OF CYSTIC FIBROSIS - Shah, Uzma; Shafiq, Yasir; Khan, Muhammad Arif Mateen (Journal of Ayub Medical College Abbottabad, 2007)
Background: Meconium ileus equivalent or the Distal Intestinal Obstruction Syndrome (DIOS) is an entity that is frequently seen in patients with cystic fibrosis (CF). In the gastrointestinal tract cystic fibrosis may produces symptoms of malabsorption and constipation. The latter may be associated with complications such as impaction and intestinal perforation. Meconium ileus and DIOS are an emergency and requires to be treated aggressively to ensure that consequences such as perforation do not occur. Method: Traditional modes of management of DIOS have included the use of laxatives, Acetylcysteine and Gastrograffin enemas. We are describing the use of oral gastrograffin in our patient seen at the Aga Khan University Hospital where small bowel obstruction was refractory to treatment. Oral gastrograffin was used once diluted in 4 times the volume of water or fruit juice with half doses given on day 2 and 3. Results: Oral gastrograffin use was followed by relief of obstruction in this patient. Conclusion: Gastrograffin use orally or rectally may be helpful in the treatment of refractions distal intestinal obstruction syndrome in cystic fibrosis. Keyword: Gastrograffin, Intestinal, Syndrome, Cystic fibrosis